Power transformer winding model for lightning impulse testing. (2017) - Župan, Tomislav; Trkulja, Bojan; Štih, Željko
Abstract: This paper presents a method for calculating the internal voltage transients useful for power transformer winding modelling. The method is based on lumped parameter model of a transformer winding and the transient response is obtained using time-domain analysis. Lumped circuit parameters are calculated using self-developed solvers which are benchmarked using professional finite element method (FEM) software. The results show that the presented approach gives satisfactory results and is computationally very fast.